1989
DOI: 10.1210/endo-124-1-552
|View full text |Cite
|
Sign up to set email alerts
|

Production and Regulation of Inhibin Subunits in Pituitary Gonadotropes

Abstract: Two related proteins, inhibin and activin, are produced and secreted by the gonads and act at the pituitary to regulate FSH secretion. In the present study, the alpha and beta B, but not the beta A, polypeptide subunits of inhibin were localized in the cytoplasm of FSH- and LH-immunoreactive (ir) gonadotropes. Ovariectomy (OVX) increased the size and number of cells immunoreactive for inhibin-alpha and -beta B as well as the mRNAs encoding these subunits. Treatment with estrogen prevented these effects. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
97
3
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(110 citation statements)
references
References 0 publications
8
97
3
2
Order By: Relevance
“…The subcellular localization of activin in the present study was in accord with those reported by Roberts et al in the rat anterior pituitary [14,15]. They found inhibin a and fi immunoreactivities in cytoplasms of gonadotropes and their costorage with LH and FSH secretory granules.…”
Section: Discussionsupporting
confidence: 93%
“…The subcellular localization of activin in the present study was in accord with those reported by Roberts et al in the rat anterior pituitary [14,15]. They found inhibin a and fi immunoreactivities in cytoplasms of gonadotropes and their costorage with LH and FSH secretory granules.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of the findings demonstrating an ubiquitous presence of a subunit mRNA in the rat pituitary [3][4][5][6][7][8], the presence and subtype of fi subunit in the rat pituitary has been controversial. So far, Meunier et al [3], Roberts et al [4] and Corrigan et al [5], and Depaolo et al [6] have all reported the fi subunit mRNA expression with a sole or a predominance of flu. Halvorson et al [9] demonstrated that NA mRNA was coexpressed with a and /3 subunits and activin type 2 receptor mRNAs in cultured rat anterior pituitary cells.…”
Section: Discussionmentioning
confidence: 99%
“…43: 403-410,1996) INHIBINS and activins are known to modulate FSH secretion from the rat anterior pituitary [1,2]. Along with their endocrine role, mainly exerted by inhibin, enough evidence has been accumulated [3][4][5][6][7] for an autocrine or a paracrine role of these peptides in FSH secretion. So far, studies demonstrating local expressions of Inhibin a and fiB subunit mRNAs [3][4][5][6][7][8], a decrease in FSH secretion by a passive immunoneutralization with activin B monoclonal antibody [5,6] or immuno-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Таким образом, повышается инкреция ФСГ, что приводит к росту фолликулов. Поэтому механизм отрицатель-ной обратной связи остается интактным, происхо-дит нормальный рост фолликулов, выбор доминант-ного фолликула, атрезия меньших по размеру фол-ликулов, что приводит в конечном счете к монофол-ликулярному росту и овуляции [9][10][11][12].…”
unclassified